SEISMIC ANISOTROPY IN EASTERN TIBET FROM SHEAR WAVE SPLITTING REVEALS CHANGES IN LITHOSPHERIC DEFORMATION - Lev E.; Long M.D.; Hilst R.D.V.D. (My University, 2006)
Knowledge about seismic anisotropy can provide important insight into the deformation of the crust and upper mantle beneath tectonically active regions. Here we focus on the southeastern part of the Tibetan plateau, in Sichuan and Yunnan provinces, SW China. We measured shear wave splitting of core-refracted phases (SKS and SKKS) at a temporary array of 25 IRIS-PASSCAL stations. We calculated splitting parameters using a multi-channel and a single-record cross-correlation method. Multiple layers of anisotropy cannot be ruled out but are not required by the data. A Fresnel zone analysis suggests that the shallow mantle (between 60 and 160 km depth) is the most likely source of anisotropy. The polarization directions reveal a pronounced transition from primarily north-south in the north (Sichuan) to mostly east-west orientations in the south (Yunnan). In the southern part of the study region, that is, south of ~ 26°N, the fast polarization directions do not correlate well with known surface features and geodetic estimates of the crustal displacement fields. Whereas GPS campaigns provide evidence suggesting north-south crustal flow across the Red River Fault, the pattern of anisotropy argues against such flow in the upper mantle. These observations support models that allow differential movement of upper crust relative to lithospheric mantle. In the northern part of the study region the relationships are more ambiguous and coherent deformation of the crust and mantle lithosphere cannot be excluded. The interpretation of the shear wave splitting results is non-unique, but we suggest that the observed N-S transition reflects a fundamental change in deformation regime across our study region. It may be related to lateral variations in lithospheric rheology, or may mark a transition from the direct impact of the continental collision to dominance of the far-field strain field associated with regional subduction processes. Understanding the nature of the lateral change in deformation regime may prove critical for our understanding the geotectonic evolution of (eastern) Tibet. © 2006 Elsevier B.V. All rights reserved.
Keywords: CONTINENTAL COLLISION; SHEAR WAVE SPLITTING; TIBETAN PLATEAU